2022
DOI: 10.48550/arxiv.2203.07397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gauge Structure of Double Field Theory follows from Yang-Mills Theory

Abstract: We show that to cubic order double field theory is encoded in Yang-Mills theory. To this end we use algebraic structures from string field theory as follows: The L ∞ -algebra of Yang-Mills theory is the tensor product K ⊗ g of the Lie algebra g of the gauge group and a 'kinematic algebra' K that is a C ∞ -algebra. This structure induces a cubic truncation of an L ∞ -algebra on the subspace of level-matched states of the tensor product K⊗ K of two copies of the kinematic algebra. This L ∞ -algebra encodes doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Reference [246] described a 'covariant colour-kinematics duality' at the level of the equations of motion. Reference [247] showed that currents (one leg off-shell) obtained from perturbative DFT satisfy a simple generalisation of the on-shell KLT relations; see [248][249][250] for related work. Regarding complete 'off-shellness', it is worth mentioning that there exist elegant and useful Lagrangians for gravity that were at least motivated by the double copy [251,252].…”
Section: Higher-order Perturbative Double Copymentioning
confidence: 99%
“…Reference [246] described a 'covariant colour-kinematics duality' at the level of the equations of motion. Reference [247] showed that currents (one leg off-shell) obtained from perturbative DFT satisfy a simple generalisation of the on-shell KLT relations; see [248][249][250] for related work. Regarding complete 'off-shellness', it is worth mentioning that there exist elegant and useful Lagrangians for gravity that were at least motivated by the double copy [251,252].…”
Section: Higher-order Perturbative Double Copymentioning
confidence: 99%